2017
DOI: 10.6026/97320630013202
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Plasma Metabolomic Biomarkers for Lung Cancer

Abstract: In drug invention and early disease prediction of lung cancer, metabolomic biomarker detection is very important. Mortality rate can be decreased, if cancer is predicted at the earlier stage. Recent diagnostic techniques for lung cancer are not prognosis diagnostic techniques. However, if we know the name of the metabolites, whose intensity levels are considerably changing between cancer subject and control subject, then it will be easy to early diagnosis the disease as well as to discover the drug. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 13 publications
1
27
1
Order By: Relevance
“…In fact, the HFD-fed mice have elevated glucose in the plasma (11). Our findings differ from human studies where lung cancer patients exhibited elevated blood levels of lactic acid when compared to healthy controls (31,32) and from in vitro studies where neoplastic cells produce high amounts of lactic acid (33). The elevation in lactic acid in cancer attributes to the Warburg Effect in which cancer cells predominantly produce their energy through a high rate of glycolysis followed by lactic acid production (12,34).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In fact, the HFD-fed mice have elevated glucose in the plasma (11). Our findings differ from human studies where lung cancer patients exhibited elevated blood levels of lactic acid when compared to healthy controls (31,32) and from in vitro studies where neoplastic cells produce high amounts of lactic acid (33). The elevation in lactic acid in cancer attributes to the Warburg Effect in which cancer cells predominantly produce their energy through a high rate of glycolysis followed by lactic acid production (12,34).…”
Section: Discussioncontrasting
confidence: 82%
“…The difference from the current study may be because we studied the early stage of metastasis, in which metastatic modules were analyzed in mm 2 in size (11). This certainly differs from studies with large tumor burden in terms of wasting and cancer metabolism (31,32). Furthermore, this downregulation of glycolysis in the presence of LLC seemed to be strong; TRF did not affect this shift in metabolism.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, it is now well established that cancer cells produce distinct chemical signatures that can be seen in tissues and biofluids [16]. As a result, a number of metabolite biomarkers that are specific to lung cancer have been discovered in a variety of biofluids, including serum/plasma, bronchial fluid, or sputum [17][18][19]. These biomarkers have frequently been discovered via metabolomics.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular energetics is important for the maintenance of lung cell function under various pathophysiological conditions. Metabolic homeostasis is vital in regulating cell proliferation and differentiation, and studies have shown that metabolic dysregulation contributes to various inflammatory responses and apoptosis . The catabolism of major nutrient substrates such as sugars, amino acids and fatty acids (FA) introduces acetyl‐CoA into the tricarboxylic acid (TCA) cycle to produce metabolites for the synthesis of nucleotides, proteins and lipids, and most importantly to generate energy.…”
Section: Metabolic Pathways Implicated In Cldmentioning
confidence: 99%
“…Towards the discovery of biomarkers and in the pursuit of improved disease characterization, metabolomics has been employed in lung diseases to study a large number of sample types including urine, plasma and serum, cerebrospinal fluid, exhaled breath condensate (EBC), bronchoalveolar lavage fluid (BALF), saliva, intact tissue as well as cells and their extracts. Urine and blood are the most commonly used biofluids for metabolomic studies as both samples contain thousands of detectable metabolic features and can be collected using minimally invasive methods.…”
Section: Metabolomic‐driven Discovery Of Biomarkersmentioning
confidence: 99%